Aplikasi Absensi Mengajar Dosen Berbasis Web Dengan Menerapkan Schedule Access Control - Ely Nuryani; Khasan Asrori; Irma Yunita Ruhiawati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The recording of lecturer attendance that has been done so far is manual and carried out on campus. However, online learning makes lecturers automatically not come to campus and take attendance online with a certain format. Online recording of lecturer absences is very ineffective and inefficient, the reason is that there are many media used by lecturers in reporting their attendance such as using messages, WhatsApp, or email. Many lecturers are late in reporting their attendance. These things make it difficult to recapitulate the presence of lecturers and for the head of study program it is difficult to monitor the lecturers who conduct lectures. To solve these problems, a teaching attendance list application was made. This application development is using the waterfall method. This application is web based using the PHP programming language and MySQL as the database. It aims so that every lecturer can access anytime and anywhere. This application is also built by implementing class schedule as an access control (schedule access control) so that lecturers can fill in attendance on time, this helps every lecturer to be orderly in doing attendance. The results of this study are the creation of applications that help facilitate lecturers in doing attendance, make it easier for staff in making lecturers' attendance and make it easier for head of study programs to monitor lecturer discipline.